Options, futures, and other derivatives - Hull, John, 1946-; Basu, S. (11th ed., 2022)
"A college textbook for courses in business, economics, financial mathematics and financial engineering. A reference book for practitioners in derivatives markets"--
Revised edition of the author's Options, futures, and other derivatives, [2018]
Includes index.
Keywords: Futures; Stock options; Derivative securities